Wakaf dan Ekonomi Hijau: Upaya Mengurangi Perubahan Iklim dan Emisi Gas Karbon - Dede Aji Mardani (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2023)
The problem of climate change is a major problem for countries because it has an impact on the quality of human life. Earth as the home of living things has undergone major and extreme changes, especially at the level of health, quality and environment. The survival of humans is to some extent influenced by climate, weather and environmental health. The aim of this research is to control climate change and global warming through a green economy and forest waqf as the instrument. With the concept of a green economy, waqf can reduce global warming, empower communities and reduce carbon emissions. Secondary data was collected from secondary sources such as literature, reports and documents related to green waqf. The results show that green waqf is highly recommended to support a green economy that has an impact on climate change. Waqf as a charitable institution in Islam is expected to play an important role in protecting against climate change and maintaining ecology. Green waqf and environmental protection can supply renewable energy, green tourist areas and play an important role in preserving the environment, raising living standards, and accelerating new economic power.